Correlation of ABO blood groups with spontaneous recanalization in acute myocardial infarction. (4th July 2017) - Lin, Xian-Liang; Zhou, Bing-Yang; Li, Sha; Li, Xiao-Lin; Luo, Zhu-Rong; Li, Jian-Jun
Abstract: Objectives. Although previous studies have demonstrated the relationship between ABO blood groups and cardiovascular disease, the association of ABO blood type with spontaneous recanalization (SR) in patients with acute myocardial infarction (AMI) has not been previously investigated. Methods. We performed an initial exploratory study on the association of ABO blood groups with the presence of SR in 1209 patients with AMI. They were divided into two groups according to the thrombolysis in myocardial infarction (TIMI) grades: no-SR group (TIMI 0–1, n = 442) and SR group (TIMI 2–3, n = 767). To confirm our primary findings, data from a second AMI population ( n = 200) was analyzed. Results. In the initial data, SR group had a significantly higher percentage of blood type O and a lower percentage of blood type A compared to the no-SR group. Multivariate logistic regression analysis showed that blood type O was positively associated with SR (odds ratio: 1.40, 95% confidence interval: 1.05–1.87, p = .02), and this finding was confirmed in our second population. Conclusion. The present study demonstrates that blood type O was independently and positively associated with an open culprit artery in patients with AMI, suggesting that the ABO blood type is not only associated with the susceptibility to coronary artery disease but also to spontaneous reperfusion in AMI patients.